PEMBATALAN PERJANJIAN PERKAWINAN OLEH SALAH SATU PIHAK DAN AKIBAT HUKUM YANG DITIMBULKAN - afni rivana mutia (Al-Hukkam: Journal of Islamic Family Law, 2022)
This study aims to analyze the difference in the ratio of legal considerations in deciding cases of cancellation of marriage agreements by one party between the Batam Religious Court Decision Number 941/PDT.G/2019PA.BTM and the Religious High Court Decision Number 50/PDT.G/2020/ PTA. PBR as well as to explain and analyze the differences in the legal consequences that arise from the cancellation of the marriage agreement. By using the judge's judgment theory, the agreement theory and the concept of the marriage agreement, the researcher tries to analyze the legal considerations of the judge in deciding the case of the cancellation of the marriage agreement and the legal consequences that arise. of the decision made. Through normative juridical research with a statutory approach, a conceptual approach, a comparative approach and a case approach. These data were collected by tracing documents in the form of primary legal materials in accordance with the problems in this study. The results of this study explain that the difference in judges' considerations lies in the evidentiary approach taken by the Panel of Judges in their legal considerations to decide cases. In deciding the case the judge considers using systematic interpretation and argumentation so that the cancellation of the agreement whose regulations have not been regulated by law can be carried out and the legal consequences arising from the judge's decision are to follow the initial legal provisions of the issue at issue in the agreement made.